Periodization in Anterior Cruciate Ligament Rehabilitation: New Framework Versus Old Model? A Clinical Commentary - Georgios Kakavas; Florian Forelli; Nikolaos Malliaropoulos; Timothy E Hewett; Panagiotis Tsaklis (International Journal of Sports Physical Therapy)
The physiological and psychological changes after anterior cruciate ligament reconstruction (ACLR) do not always allow a return to sport in the best condition and at the same level as before. Moreover, the number of significant re-injuries, especially in young athletes should be considered and physical therapists must develop rehabilitation strategies and increasingly specific and ecological test batteries to optimize safe return to play. The return to sport and return to play of athletes after ACLR must progress through the recovery of strength, neuromotor control, and include cardiovascular training while considering different psychological aspects. Because motor control seems to be the key to a safe return to sport, it should be associated with the progressive development of strength, and cognitive abilities should also be considered throughout rehabilitation.